The use of 3D printing in cardiac surgery - Ong, Chin Siang; Hibino, Narutoshi (Journal of Thoracic Disease; Vol 9, No 8 (August 28, 2017): Journal of Thoracic Disease, 2017)
In this issue, Chen et al. present a case report where a patient with a right-sided aortic arch, Kommerell’s diverticulum (KD) and an aberrant left subclavian artery underwent surgical repair, and the surgeons printed a patient-specific three-dimensional (3D) model before surgery to serve as a surgical guide. Using the 3D printed model, they managed to select the size of the frozen elephant trunk for implantation (32 mm) and visualize the aorta and its branches pre-operatively, to decide on the section to resect, reducing operative time. The patient made an uneventful recovery and postoperative computed tomography (CT) scan of the aortic arch demonstrated graft shape, position and patency.